Self-perceived communication competence and communication apprehension: A study of Indonesian college students - Adaninggar Septi Subekti (Universitas Islam Sultan Agung, 2020)
Considering the important role of Individual Differences (IDs) factors in variations in the ultimate success of learners learning second language (L2, this study investigated Indonesian college students’ two ID components, self-perceived communication competence (SPCC) and their communication apprehension (CA), in English as L2. Several rationales become the basis of the present study. Despite the importance of learners’ SPCC in L2 learning as suggested by several empirical studies outside Indonesia, there have not been any specific study investigating learners’ SPCC in the Indonesian context despite the country being the home of one of the largest number of L2 speakers of English in the world. As a seminal study in the context, the study using quantitative methods enables generalisation which could pave a way for further studies in the field in the Indonesian context. A total of 276 non-English major college students participated in the study in a survey using probability random sampling. Using descriptive statistics in SPSS 21, the study found that learners had medium level of SPCC and medium level of CA. Through correlation formula, the study also found that there was moderate significant association between learners’ SPCC and their CA. Through regression analysis, it was found that their SPCC could predict 23% of variance in their CA. The findings urge teachers to provide as many learning opportunities as possible in enjoyable learning environment to increase learners’ perception of their capability, in turn boosting their confidence to speak in English. Based on the findings and several limitations of the study, several suggestions of future studies are presented.